KARAKTER RELIGIUS-TOLERAN JAMAAH TABLIGH - Irpan Irpan; Uswatun Uswatun Uswatun; Novianti Novianti (Mudabbir: Jurnal Manajemen Dakwah, 2020)
Research on the religious-tolerant character of the jamaah tabligh, namely research with through interview and observation methods. Jamaah tabligh is a transnational da'wah movement. Jamaah tabligh does not only focus on the relationship between humans and the creator, but also instills a tolerant character towards other religions. The tolerant attitude instilled by the jamaah tabligh becomes a character that is inherent in every action so that it becomes very open to the parties. The delivery of da'wah messages according to the jamaah tabligh, can be conveyed to informants without differentiating between social status or profession, because the principle of the jamaah tabligh in its preaching is the invitation of humans to return to the path of Allah. The religious-tolerant character of the jamaah tabligh is part of the da'wah strategy that was practiced by the Prophet, by not condemning other people in his preaching activities. The religious-tolerant character of the jamaah tabligh is also the answer for some people who accuse the tabligh congregation of being a movement that is antipathy to other groups that are not in line with the method of proselytizing. The religious-tolerant character of the jamaah tabligh can be seen from the six new basics as the principle of preaching, namely, Al kalimah toyyibah, upholding prayer, knowledge and remembrance, glorifying fellow Muslims, sincere and finally Khuruj Fi Sabilillah